Mitigating Function in Verb Forms Conveying Doubt in the Chilean PRESEEA Semi-Structured Interviews Corpus - Consuelo Gajardo Moller; Silvana Guerrero González; Javier González Riffo; Daniela Ibarra Herrera (Ikala: Revista de Lenguaje y Cultura, 2023)
This article analyzes the attenuating function of verbal forms expressing doubt in semi-structured interviews found in the PRESEEA corpus of Santiago de Chile. 36 interviews, collected in 2009, were analized taking into account the participants image, speech acts, and discursive positions. Verb sociolinguistic variation —as determined by sex, age, and education level— was also examined. The main doubt expressions with an attenuating function found include doxastic verbs such as creer (“believe”) and suponer (“suppose”), the modal verbs deber (“must” or “should”) and poder (“could”, “might”), and the verb expressing lack of knowledge no saber (“to not know”). These expressions occur when speakers express their true point of view as a doubt, or when they report a state of affairs. The result is a speaker directed towards the “other”, who does not want to expose their image to their interlocutor, when the speaker expresses opinions about controversial topics or when they report facts that they prefer not to express openly. Sociolinguistic variation is scarce and is mostly related to age.